Image Measurement of Electrolyte Volatilized Phenomenon in MCFC - YODO, Tadakatsu; OKAWA, Hideaki; YAMAUCHI, Makoto; SUGIURA, Kimihiko; TANIMOTO, Kazumi (Journal of the Visualization Society of Japan, 2005)
Volatilizing of the molten salt is one of factors, that control the life performance of Molten Carbonate Fuel Cell (MCFC). Volatilizing of the molten salt promotes the cross-leak and the corrosion of the metallic component. Moreover, the piping blockage is caused by volatile matter's solidifying. Especially, because the reforming catalysts filled to the anode channel are polluted by volatile matter of the molten salt in Direct Internal Reforming Molten Carbonate Fuel Cells (DIR-MCFC), volatilizing of the molten salt is a weighty subject. However, neither the behaviour nor the volatilization volume of molten salt volatile matter has been elucidated. These reasons are that molten salt volatile matter that has the strong alkalinity cannot be supplied directly to the analyzer, and as its volatilization volume is a small amount, the analysis accuracy is bad. Therefore, we tried to elucidate the behaviour of vaporized alkali hydroxide by using the image measurement technique that is a non-contact measurement method. As a result, we succeed visualization for the three-phase interface and could measure the volatile phenomenon of MCFC electrolyte. This result proves an actual polluted phenomenon.